Advances in mergers and acquisitions. Volume 18 - Cooper, Cary L.,; Finkelstein, Sydney, (Advances in mergers and acquisitions ;)
Advances in Mergers and Acquisitions stands out from the competition due to its focus on three key characteristics: studies from scholars in different countries, with different research questions, relying on different theoretical perspectives. Such a broad and inclusive approach to mergers and acquisitions is not easily replicated in academic journals, with much narrower mandates and metrics. The chapters published in this volume provide cutting edge ideas by leading scholars, and help to inform mergers and acquisitions research around the world.Volume 18 of this annual series explores a range of issues that include: why the success rate of M&As is still limited; how Boards influence M&A activity; what the role of M&A advisors is; the role of diversity in the context of M&As; stakeholder relationships in the context of M&As; why research has not focussed on family businesses in the M&A field as much as it should; making M&As less risky as a strategic investment; merging cities; pre-merger and acquisition strategies and finally, how 'value' has been used or not used in M&As.